“Poor but Happy”: Life Struggle and the Meaning of Happiness among the Poor in Yogyakarta - Lu'lu' Husnul Muthia; M. Falikul Isbah (JSW (Jurnal Sosiologi Walisongo), 2022)
Results from the 2019 Indonesian National Socioeconomic Survey showed that the poverty rate in the Special Region of Yogyakarta was 11.44 %, higher by 2.22% than the 9.22% national average. However, the National Human Happiness Index in 2014 and 2017 showed that the residents of Yogyakarta were among the top ranks. This study aims to describe the poor empirically and the meaning of happiness for them. Applying the qualitative method using a narrative approach, the results revealed that the informants were not happy living in poverty but were content with their lives for reasons attributable to the belief system and local culture. In the Javanese language, this attitude is called ‘nerimo’, which translates into ‘accepting the situation’. They practice this to improve their psychological well-being.